What is the International Dimension of International Finance? - Brealey, Richard A.; Cooper, Ian A.; Kaplanis, Evi (Review of Finance, 1999)
Richard A. Brealey, Ian A. Cooper, Evi Kaplanis; What is the International Dimension of International Finance?, European Finance Review, Volume 3, Issue 1,